Enzymatically Produced Liquid Crystalline Phases for Encapsulation and Extended Release of Ibuprofen and Aspartame - Jiang,Xiaotong (2025)
In order to design and investigate the effects of vegetable oil based enzymatically produced liquid crystalline phases (LCPs), oat oil with 15% and 50% polar lipids contents (PL15, PL40) and with different storage conditions were incubated with Lipozyme TL and CalB. PL40 based LCPs were further investigated incorporating 1-10% aspartame (ASP) or ibuprofen (IBU) and all of the LCPs samples were analyzed with SAXS to study the nanostructures. GC-FID was used to analyze the lipid ratios of the original oil sample and the LCPs samples. pH-stat titration experiment was performed to study the effect of LCPs properties under a controlled pH of 7. In order to study the effect of LCPs in simulated digestion tract, PL40, coconut oil based samples were studied in simulated intestinal fluid.
Keywords: LCPs; lipids; structure; ibuprofen; drug release; biotechnology